2016
DOI: 10.1111/imj.12991
|View full text |Cite
|
Sign up to set email alerts
|

Associations of demographic and behavioural factors with glycaemic control in young adults with type 1 diabetes mellitus

Abstract: In young adults with T1DM, geographical separation, socioeconomic disadvantage and risk-taking behaviours did not influence glycaemic control. Longer duration of diabetes identifies young adults at higher risk of poor control, while attendance at a multidisciplinary clinic and engagement in work or study was associated with better glycaemic control. Additional studies are warranted to clarify the role of behavioural interventions to improve diabetes management in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
3
16
0
1
Order By: Relevance
“…An association between low SES (as measured by education, social class or income) and poorer glycaemic control was found in nine of the twelve studies [10;16;19;21;31;36;40;43;51]. Two studies found no SES association with glycaemic control [17;35]. …”
Section: Resultsmentioning
confidence: 99%
“…An association between low SES (as measured by education, social class or income) and poorer glycaemic control was found in nine of the twelve studies [10;16;19;21;31;36;40;43;51]. Two studies found no SES association with glycaemic control [17;35]. …”
Section: Resultsmentioning
confidence: 99%
“…Our justification for using ketoacidosis was that episodes are associated with poor disease control and poor adherence to treatment [6]. We considered clinic attendance to be an important part of satisfactory transitional care because it correlates with a better disease outcome [23]. Clinic and annual retinal screening attendance are markers of positive health behaviour and are both recommended by the National Institute of Health and Care Excellence (NICE) guidelines for transition services and management of young people with diabetes [27].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on how best to assess a satisfactory clinical course during transition. Following discussion among the authors, the wider Transition Research Collaborative group and a review of the literature [11,23,24], a set of criteria based on collected clinical and attendance data was established to define a satisfactory clinical course. The four markers were: glycaemic control (HbA 1c ), any episode of diabetic ketoacidosis, clinic attendance and retinal screening attendance.…”
Section: Clinical Course During Transitionmentioning
confidence: 99%
“…They included: The Problems Areas in Diabetes (PAID) (20 items) with scores ≥ 40 representing severe diabetes-related distress (12,13), and a score ≥ 30 representing significant diabetes-related distress; The Kessler 10 (K10; 10 items) assessing psychological distress, focusing on depression and anxiety symptoms, ow levels of distress (10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21), high level (22)(23)(24)(25)(26)(27)(28)(29) and very high are defined (14,15); The WHO-5 Well-being Index (5 items) assessing quality of life, with scores ≤ 13 indicative of low well-being, and scores < 8 indicative of depression (16,17) (22), (23) were compared to USA normative data (non-diabetic), and 4 items assessed financial concerns.…”
Section: Methodsmentioning
confidence: 99%
“…A multidisciplinary team approach seems indicated with evidence this model is related to better glycaemic control (10), more support, lower diabetes-related distress, and higher satisfaction with their diabetes care than those seeing a private endocrinologist, general practitioner or other provider (11).…”
Section: Accepted Articlementioning
confidence: 99%